Comparison of The Income of The Stebis Igm Academic Community During The Covid-19 And New Normal Pandemic - Fadilla Fadilla; Havis Aravik (Institut Agama Islam Negeri Padngsidimpuan, 2022)
This study aims to determine the difference in the income of the STEBIS IGM academic community during the covid 19 pandemic and the new normal from the Chair to the OB. The methodology used is a two-sample t-test. The results of the significance of the t-paired t-test show the number 0.000. This figure is smaller than 0.05, which means that there is a difference in the salaries of STEBIS employees during the covid pandemic and the new normal. The difference is also very visible from the increase in the average salary of employees by 40% from Rp. 3,470,000. to IDR 5,300,000. The reason for the increase in employee salaries is because the chairman of the foundation wants to motivate employees so that they can improve the quality of their work in the field of higher education tri dharma and new student admissions.